Dr. Salim Yusuf: A Critical Look at Cardiovascular Disease - Campbell, Jordan; Dhillon, Sheiry; Foster, Caylea; Naik, Hiten (The Meducator, 2012)
Dr. Salim Yusuf, MD DPhil (Oxford), is a Professor of Medicine (Cardiology) and Clinical Epidemiology & Biostatistics at McMaster University. He is the director of the Population Health Research Institute and the Vice-President of Research and Chief Scientifc Officer, Hamilton Health Sciences. He was elected fellow of the Royal Society of Canada, and also holds a Research Chair in Cardiology from the Heart and Stroke Foundation of Ontario. His recent research interests include societal, biologic and genetic determinants of population health in developing populations, specifically in the realm of cardiovascular disease. Dr. Yusuf is regarded as a pioneer in cardiovascular disease research and epidemiology in general. By conducting ambitious, multinational studies, he has been able to take fundamental questions and ask them on a global scale. His studies have involved over 83 countries in all inhabited continents of the world.